The influence of serve characteristics on performance in men's and women's high-standard beach volleyball - Busca, B.; Moras, G.; Pena, J.; Rodriguez-Jimenez, S. (Journal of Sports Sciences, 2012)
The precise influence of serve type and serve ball speed on beach volleyball performance is unclear. We examined the relationship between serve type and speed and their effectiveness during the 2008 Men's and Women's Open World Tour Tournament. Three hundred and seventy-eight and 375 serves performed by men and women respectively from the main draw tournament were analysed. Serve speed was recorded using a radar gun. Two expert observers recorded serve speed, serve mode, serve effectiveness and rally outcome. There was no relationship between serve speed and its effectiveness for men (r = -0.047, P > 0.05) and for women (r = -0.048, P > 0.05). However, there was a relationship between serve ball speed and its effectiveness both for men and women, when speed was categorised into three groups. There was a better balance between negative and positive outcomes at medium speeds for men and at low and high speeds for women. There was a relationship between ranking and serve ball speed only for women and between ranking and type of serve for both genders. There was no relationship between rally outcome and serve effectiveness. The combination of high ball speed and jump serve is characteristic of high ranking women but not of men.